1993
DOI: 10.1111/j.1476-5381.1993.tb13813.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the cardiovascular and neural activity of endothelin‐1, −2, −3 and respective proendothelins: effects of phosphoramidon and thiorphan

Abstract: 1 In the anaesthetized, ganglion-blocked rat, intravenous boluses of endothelin-1, endothelin-2 and endothelin-3 induced a transient hypotensive effect followed by a potent long lasting pressor response (ED_sommHg: 0.72 ± 0.05, 1.8 ± 0.2 and 2.7 ± 0.3 nmol kg-', respectively). The maximal effect for the three peptides was of a similar order of magnitude (,&MAP: 84 to 89 mmHg). Neither of these effects was influenced by phosphoramidon or thiorphan (10 mg kg-', i.v.).2 Intravenously administered big-endothelin-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…All these responses were blocked by phosphoramidon, but the ECE/NEP inhibitor had no effect on the actions of the mature peptide. Similar results were obtained in the anesthetized, ganglion-blocked rat, where intravenous bolus doses of Big ET-2 were compared with Big ET-1 where the cardiovascular actions of both peptides were prevented, as expected, by phosphoramidon but not thiorphan ( Mattera et al, 1993 ).…”
Section: Endothelins and Sarafotoxinssupporting
confidence: 75%
“…All these responses were blocked by phosphoramidon, but the ECE/NEP inhibitor had no effect on the actions of the mature peptide. Similar results were obtained in the anesthetized, ganglion-blocked rat, where intravenous bolus doses of Big ET-2 were compared with Big ET-1 where the cardiovascular actions of both peptides were prevented, as expected, by phosphoramidon but not thiorphan ( Mattera et al, 1993 ).…”
Section: Endothelins and Sarafotoxinssupporting
confidence: 75%
“…Similar results were obtained in the anaesthetized, ganglion‐blocked rat, where intravenous bolus doses of Big ET‐2 were compared with Big ET‐1. The onset of the vasopressor effect was more rapid (5–6 min) for the latter than that of Big ET‐2 (10–13 min) but the actions of both peptides were blocked as expected by phosphoramidon but not thiorphan (Mattera et al ., 1993). In renal adenocarcinoma cells producing high levels of ET‐2, the presence of ECE was confirmed by sequencing (Yorimitsu et al ., 1992; 1995).…”
Section: Does Et‐2 Have a Separate Synthesis From Other Et Peptides?mentioning
confidence: 67%
“…a phosphoramidon-sensitive pressor effect, demonstrating an interspecies variation in the ECE activity (Gardiner et al, 1992;Matsumura et al, 1993;Mattera et al, 1993;Pollock et al 1993). Furthermore, Matsumura et al (1993) have suggested that different conditions of anaesthesia as well as the use of a ganglion blocker enhanced the pressor activity of big-endothelin-3 in the rat model.…”
Section: Introductionmentioning
confidence: 99%